A case report of congenital scoliosis associated with situs inversus totalis. Issue 50 (December 2017) - Zhu, Ce; Huang, Shishu; Zhou, Chunguang; Yang, Xi; Wang, Lei; Ling, Tingxian; Liu, Limin; Song, Yueming
Abstract: Rationale: Situs inversus totalis is a rare anomaly disease in which the organs in the chest and abdomen are positioned in a mirror image reversal of normal positions. Although this has been confirmed to be associated with spinal abnormalities, reports about situs inversus totalis with congenital scoliosis remain limited. Patient concerns: We present a 9-year-old girl having congenital scoliosis associated with situs inversus totalis. Diagnoses: She also had other associated anomalies: ventricular septal defect, mild restrictive ventilatory dysfunction, hydronephrosis, and syringomyelia. Her preoperative Cobb angle (T11–L3) was 78°. Interventions: She received single growing rods treatment and subsequent posterior spinal fusion correction surgery for her scoliosis. Outcomes: The coronal Cobb angle of the main curve was corrected to 20° postoperatively and no obvious loss of spinal corrective angle was identified 1 year after the correction surgery. Lessons: Growing rods technique could be a safe and effective alternative for the treatment of scoliosis associated with situs inversus totalis. In the correction of left-sided lumbar curve of this kind of patients, the risks of aorta impingements should not be neglected when placing pedicle screws on the concave sides.